Alkylimidazolium Based Ionic Liquids: Impact of Cation Symmetry on Their Nanoscale Structural Organization - Rocha, Marisa A. A.
Aiming at evaluating the impact of the cation symmetry on the nanostructuration of ionic liquids (ILs), in this work, densities and viscosities as a function of temperature and small wide angle X-ray scattering (SWAXS) patterns at ambient conditions were determined and analyzed for 1-alkyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (asymmetric) and 1,3-dialkylimidazolium bis(trifluoromethylsulfonyl) imide (symmetric) series of ionic liquids. The symmetric IL series, [ChinCNnim][NTf2], presents lower viscosities than the asymmetric [C-N/2 C-N/2 im][NTf2] counterparts. For ionic liquids from [C(1)C(1)im][NTf2] to [C(6)C(6)im][NTf2], an odd even effect in the viscosity along the cation alkyl side chain length was observed, in contrast with a linear increase found for the ones ranging between [C(6)C(6)im][NTf2] and [Ci(10)C(10)im][NTf2]. The analysis of the viscosity data along the alkyl side chain length reveals a trend shift that occurs at [C(6)Cim][NTf2] for the asymmetric series and at [C6C6im][NTf2] for the symmetric series. These results are further supported by SWAXS measurements at ambient conditions. The gathered data indicate that both asymmetric and symmetric members are characterized by the occurrence of a distinct degree of mesoscopic structural organization above a given threshold in the side alkyl chain length, regardless the cation symmetry. The data also highlight a difference in the alkyl chain dependence of the mesoscopic cluster sizes for symmetric and asymmetric cations, reflecting a different degree of interdigitation of the aliphatic tails in the two families. The trend shift found in this work is related to the structural segregation in the liquid after a critical alkyl length size (CALS) is attained and has particular relevance in the cation structural isomerism with higher symmetry.